Electrical properties of transferred graphene films on pre-treated polyimide substrate by inductively coupled plasma. (November 2016) - Kim, Jae-Kwan; Kang, Kyung Ho; Lee, Ji-Myon
Abstract: In this study, the effects of the pre-treatment of PI films using inductive coupled plasma, according to the gas species, on the electrical properties of a graphene/PI substrate system were investigated. The surface treatment of PI films using inductively coupled O2, Ar, CH4, and CHF3 plasma was performed. It was found that surface morphology and hydrophobicity are critically important substrate conditions that determine the improvement of the electrical properties of graphene transferred onto the plasma-treated PI substrate. Compared to the electrical properties of untreated PI, the CH4 and CHF3 plasma treated samples showed enhanced electrical conductivity of the graphene devices. However, the electrical conductivities of the PI treated by Ar and O2 plasma were degraded. CHF3 plasma treatment leads to the sheet resistance of 528 Ω/sq, which is the best result in this experiment. The enhanced electrical properties of the graphene on CHF3 - and CH4 -treated PI film was attributed to the reduced roughness and the removal of CO and OH chemical species by hydrophobization of the PI substrate. The fluorine groups led to a decrease of the surface free energy of the PI films, which resulted in the lowest sheet resistance. Graphical abstract: